1987
DOI: 10.1104/pp.85.3.716
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR Study of Elicitor Treated Phaseolus vulgaris Cell Suspension Cultures

Abstract: ABSTRACIThe addition of an elicitor (glucan) to Phaseolus vulgaris cell suspension cultures increased the formation of the phytoalexin phaseollin. Intracellular pH and phosphate concentrations were studied with 31P nuclear magnetic resonance spectroscopy on elicitor-treated cells which were aerated during the nuclear magnetic resonance measurement. The pH of the vacuole and to a lesser extent the pH of the cytoplasm were affected at 10 minutes after elicitor addition; a decrease in pH from 53 to 4.8 was noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…The same applies to the phaseollin-producing P. vulgaris cells of Ojalvo et al (1987). In L. flavum cells, in which production depends solely on the cell line under observation and no extemal stimulus is needed, a lower cytoplasmic pH was also observed for the producing cells (Table 111).…”
Section: Cytoplasmic Acidification and Secondary Metabolite Productionmentioning
confidence: 75%
See 1 more Smart Citation
“…The same applies to the phaseollin-producing P. vulgaris cells of Ojalvo et al (1987). In L. flavum cells, in which production depends solely on the cell line under observation and no extemal stimulus is needed, a lower cytoplasmic pH was also observed for the producing cells (Table 111).…”
Section: Cytoplasmic Acidification and Secondary Metabolite Productionmentioning
confidence: 75%
“…Cytoplasmic acidification upon activation cQ a defense response by a glucan elicitor has also been observed in Phaseolus vulgaris cells (Ojalvo et al, 1987) and in parsley cells by a Phyfophthora elicitor (Kneusel et al, 1989), whereas pH decreases in the total cell sap of tobacco cells were detected after treatment with Pseudomonas sp. (Atkinson et al, 1985).…”
Section: Cytoplasmic Acidification and Secondary Metabolite Productionmentioning
confidence: 99%
“…It has been reported that these early events (ion leakage and extracellular alkalinization) are correlated with a decrease in intracellular pH (22) and a depolarization of the plasma membrane (23,24). These responses could result from either …”
Section: Discussionmentioning
confidence: 99%
“…A transient decrease of intracellular pH has been observed repeatedly (Ojalvo et al, 1987;Kneusel et al, 1989;Guern et al, 1992;Mathieu et al, 1996a) among the changes in the ionic composition after elicitor contact, with only a few exceptions (Horn et al, 1992). This raises the question of whether changes in the intracellular pH could be involved in the signal path toward the elicitation of phytoalexin biosynthesis.…”
mentioning
confidence: 99%